2010
DOI: 10.1016/j.physbeh.2009.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A similar pattern of neuronal Fos activation in 10 brain regions following exposure to reward- or aversion-associated contextual cues in mice

Abstract: JOHNSON, Z.V., A.A. REVIS, M.A. BURDICK, AND J.S. RHODES. A similar pattern of neuronal Fos activation in 10 brain regions following exposure to reward-or aversion-associated contextual cues in mice. PHYSIOL BEHAV 00(0) 000-000, 2009 -Relapse triggered by drug-paired cues is a major obstacle for successful treatment of drug abuse. Patterns of brain activation induced by drugpaired cues have been identified in human and animal models, but lack of specificity poses a serious problem for craving or relapse interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
2
21
1
Order By: Relevance
“…Pre-conditioning preference times did not significantly differ between experimental groups, being 525±24 for SL327 (0 mg/kg)+lithium (0 mg/kg), 511±14 for SL327 (25 mg/kg)+lithium (0 mg/kg), 525±27 for SL327 (50 mg/kg)+lithium (0 mg/kg), 553±16 for SL327 (0 mg/kg) + lithium (150 mg/kg), 557 ± 11 for SL327 (25 mg/kg)+lithium (150 mg/kg), and 542±22 s/900 for SL327 (50 mg/kg)+lithium (150 mg/kg) groups (F(1, 29)= 1.86, NS). In agreement with previous observations (Acquas et al 1989;Acquas and Di Chiara 1994;Ventura et al 2007;Johnson et al 2010), lithium elicited a negative side preference shift from 553±16 to 380±28 s/900 at the post-conditioning test (p<0.05). Repeated measures, threeway ANOVA of the effects of SL327 and lithium, with preference times (pre-and post-conditioning) as repeated dependent measures and with pre-treatment (SL327 0, 25, and 50 mg/kg) and treatment (lithium 0 and 150 mg/kg) doses as independent measures, revealed a significant effect of time (F 1, 29 =9.64, p<0.004) and significant treatment by time (F 1, 29 =14.97, p <0.0005) and pre-treatment by treatment by time (F 2, 29 =3.68, p<0.037) interactions.…”
Section: Resultssupporting
confidence: 93%
“…Pre-conditioning preference times did not significantly differ between experimental groups, being 525±24 for SL327 (0 mg/kg)+lithium (0 mg/kg), 511±14 for SL327 (25 mg/kg)+lithium (0 mg/kg), 525±27 for SL327 (50 mg/kg)+lithium (0 mg/kg), 553±16 for SL327 (0 mg/kg) + lithium (150 mg/kg), 557 ± 11 for SL327 (25 mg/kg)+lithium (150 mg/kg), and 542±22 s/900 for SL327 (50 mg/kg)+lithium (150 mg/kg) groups (F(1, 29)= 1.86, NS). In agreement with previous observations (Acquas et al 1989;Acquas and Di Chiara 1994;Ventura et al 2007;Johnson et al 2010), lithium elicited a negative side preference shift from 553±16 to 380±28 s/900 at the post-conditioning test (p<0.05). Repeated measures, threeway ANOVA of the effects of SL327 and lithium, with preference times (pre-and post-conditioning) as repeated dependent measures and with pre-treatment (SL327 0, 25, and 50 mg/kg) and treatment (lithium 0 and 150 mg/kg) doses as independent measures, revealed a significant effect of time (F 1, 29 =9.64, p<0.004) and significant treatment by time (F 1, 29 =14.97, p <0.0005) and pre-treatment by treatment by time (F 2, 29 =3.68, p<0.037) interactions.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies also identified brain regions in which brief behaviors of opposite valences activated spatially intermingled populations of Fos+ neurons (Johnson et al, 2010; Kollack-Walker and Newman, 1995; Kovacs, 1998; Lin et al, 2011; Veening et al, 2005; Wu et al, 2014; Xiu et al, 2014). Thus, tools that can determine whether the same or different ensembles of neurons are activated and express Fos in different contexts or behaviors, and can manipulate the activated neurons to determine their causal functions are highly desired.…”
Section: Introductionmentioning
confidence: 92%
“…injections in a volume of 10 ml/kg. Dose was chosen based on the literature and was prepared according to the salt not the base form [12, 13, 43, 44]. …”
Section: Methodsmentioning
confidence: 99%
“…We used the same unbiased procedure as previously published by our lab [12, 13, 43] based on Cunningham’s apparatus and experimental design [45] and as previously detailed in our other work [12, 13, 43]. Within each treatment group, mice were counterbalanced with respect to the conditioned stimulus (CS+GRID or CS+HOLE) and experienced cocaine on GRID (CS+GRID) or cocaine on HOLE (CS+HOLE) texture and saline on the alternate texture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation